Are testicular sperms superior to ejaculated sperms in couples with previous ART failure due to high rate of fragmented embryos? A retrospective cohort study - Jiang, Ling-Ying; Kong, Fei-Fei; Yao, Lv; Zhang, Fu-Xing; Wang, Sha-Sha; Jin, Xiao-Ying; Tong, Xiao-Mei; Zhang, Song-Ying (Frontiers in Surgery, 2023)
Objective: The aim was to clarify whether using testicular sperm reduces embryo fragmentation and improves cycle outcomes. Methods: Fragmented embryo was defined as an embryo in which fragments account for more than one third of the embryonic surface area. High rate of fragmented embryos was defined by a proportion of fragmented embryos higher than 50%. We recruited infertile couples who had undergone at least one ovarian stimulation cycle using ejaculated sperm but failed to conceive due to high rate of fragmented embryos in each previous cycle. After fully informed consent, the couples agreed to obtain testicular sperm by testicular puncture and use testicular sperm for intracytoplasmic sperm injection (ICSI). The normal fertilization rate, transferable embryo rate, fragmented embryo rate and cycle outcomes were compared between ejaculated sperm group (EJA-sperm group) and testicular sperm group (TESTI-sperm group). Results: Twenty-two couples who agreed to participate in our study underwent 32 ICSI cycles with ejaculated spermatozoa and 23 ICSI cycles with testicular spermatozoa. Embryo transfers were cancelled in 8 ejaculated cycles and 4 testicular cycles because of no transferable embryos. There were no significant differences in age, normal fertilization rate and high-quality embryo rate between ejaculated and testicular groups. The transferable embryo rate and implantation rate in TESTI-sperm group were significantly higher than those in EJA-sperm group (36.9% vs. 22.0%, p<0.01; 34.2% vs. 0%, p<0.001). The fragmented embryo rate in TESTI-sperm group was significantly lower than that in EJA-sperm group (61.2% vs. 75.7%, p<0.05). Conclusion: Our small retrospective cohort study suggests that using testicular sperm may be a recommended option for couples with previous ART failure because of high rate of fragmented embryos. Large samples, multicenter studies or randomized controlled trial (RCT) are needed to further confirm the superiority of testicular sperm.